Layered Ti3C2Tx / MXene loaded FeCo nanoparticle composite material, preparation method and application
By combining FeCo nanoparticles with Ti3C2Tx/MXene materials to form a composite material with a layered structure, the problem of difficulty in developing high-performance terahertz absorbing materials in the prior art is solved, and effective absorption effect in a wide terahertz frequency band is achieved.
Patent Information
- Application Number
- CN202411947561.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
Smart Images

Figure CN119795689A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials and particularly provides a layered Ti3C2T x / MXene-loaded FeCo nanoparticle composite materials, preparation methods and applications. Background Art
[0002] Terahertz waves with frequencies between 0.1 and 10 THz are widely used in medical imaging, wireless communications, security inspections, and other fields due to their ultra-wideband spectrum, low electron energy, and spectral fingerprints. While terahertz technology brings convenience, electromagnetic wave pollution has also had a huge impact on human health, environmental development, and information security. Therefore, researchers are paying more and more attention to the field of wave absorption. The use of ideal wave absorbing materials can achieve the effect of absorbing excess electromagnetic waves. It is particularly important to develop a high-performance terahertz wave absorbing material with light weight, thin thickness, low reflection, and wide effective absorption bandwidth.
[0003] MXene is a two-dimensional material composed of transition metal elements and carbides or nitrides. Its chemical formula is M n+1 X n T x (n=1, 2, 3), where M represents an early transition metal element (Ti, Mo or Zr, etc.), X represents a carbide or a nitride, and T x is a surface group (-OH, -F or -O, etc.). Ti3C2T x As the earliest synthesized MXene, it has attracted widespread attention and is obtained by etching Al layer elements in Ti3AlC2. x MXene has a unique layered structure, excellent dielectric capacity and abundant surface groups, and has been regarded as an ideal alternative material for TEMW interaction, especially the abundant surface groups are Fe 2+ and Co 2+ Metal ions such as Ti3C2T provide the most suitable ligands. x / MXene has become one of the most widely studied MXene materials due to its excellent electrical conductivity and good terahertz absorption performance. FeCo alloy is an excellent soft magnetic material with low coercivity and high saturation magnetic susceptibility. By introducing FeCo nanoparticles, the Ti3C2T x / MXene itself has ultra-high conductivity. On the other hand, it is also beneficial to adjust electromagnetic parameters and optimize impedance matching. x Combining MXene with other magnetic materials to form a magneto-dielectric composite material is an effective way to achieve electromagnetic wave absorption. So far, there has been no related report.
[0004] Patent CN117362856A discloses an electromagnetic shielding composite material and its preparation method, wherein polymer core-shell microspheres are prepared by copolymerizing maleic anhydride with styrene and divinylbenzene respectively, and then hollow microspheres are obtained by eluting the microsphere template core with acetone. After the hollow microspheres are dispersed in water, they are mixed and filtered with a MXene aqueous dispersion to add the hollow microspheres between the MXene sheets to form a multi-level structure that is beneficial to electromagnetic shielding. However, it does not involve applications in wave absorption.
[0005] Patent CN114454573A discloses a Ti3C2T x / MXene / GO heterogeneous membrane and preparation method and application thereof, the heterogeneous membrane is composed of GO layer and Ti3C2T x The three-layer structure film with microscopic heterogeneous interface formed by the staggered stacking of Ti3C2T x / MXene / GO heterogeneous film not only has good electromagnetic shielding performance, GO can also protect Ti3C2T x / MXene is not oxidized, which makes it long-lasting and can be used in the field of electromagnetic shielding. It also does not involve applications in wave absorption. Summary of the invention
[0006] The synthesis of layered Ti3C2Tx / MXene loaded FeCo nanoparticle composites has great application prospects in microwave absorption and is in urgent need of development and research.
[0007] The present invention adopts an electrostatic self-assembly method to combine FeCo nanoparticles prepared by a hydrothermal method and Ti3C2T prepared by an in-situ etching method. x / MXene is combined to obtain a composite material with a layered structure. Because of the flexible, easy-to-control, safe and reliable reaction conditions, nanocomposites that do not require subsequent treatment, are environmentally stable, have special structures and adjustable dielectric properties can be prepared in large quantities and can be used for terahertz electromagnetic wave absorption.
[0008] The present invention aims to provide a composite material of layered Ti3C2Tx / MXene loaded with FeCo nanoparticles and its application, that is, FeCo nanoparticles and Ti3C2Tx are prepared by hydrothermal method, in-situ etching method and electrostatic self-assembly method. x / MXene composites, in which FeCo nanoparticles are loaded into Ti3C2T x The surface and interlayers of MXene materials do not require subsequent treatment and have excellent wave absorbing properties.
[0009] The technical solution of the present invention is as follows:
[0010] Layered Ti3C2Tx / MXene loaded FeCo nanoparticle composite material, the structure is composed of magnetic nanoparticles and wrinkled Ti3C2T x The layered structure of / MXene contains FeCo magnetic nanoparticles inside the composite material, and the FeCo magnetic nanoparticles are loaded into Ti3C2T x / MXene materials, so that the magnetic particles are dispersed with each other.
[0011] The FeCo loading mass percentage in the composite material structure is 10-30wt.%.
[0012] The interlayer spacing in the composite material structure is 150-190 nm; the diameter of the FeCo magnetic nanoparticles is 15-20 nm.
[0013] The present invention also provides the method of combining magnetic nanoparticles with two-dimensional layered structure Ti3C2T x The preparation method of the composite material combined with / MXene is to first prepare FeCo spherical nanoparticles by hydrothermal method using sulfates and chlorides of Fe and Co; secondly, Ti3AlC2 MAX material is used as a precursor to prepare Ti3C2T x / MXene materials; finally, the magnetic nanoparticles were assembled into two-dimensional layered Ti3C2T x / MXene are combined to obtain composite materials.
[0014] Solved Ti3C2T x The technical difficulties in the preparation of / MXene composite materials make the preparation process simple, easy to operate, low-cost, safe and reliable.
[0015] Wherein: the mass ratio of sulfate and chloride of Fe and Co is 1:4 and FeCo nanoparticles are obtained by hydrothermal method;
[0016] The mixed solution of HCl+LiF is stirred in a stirrer for 0 to 1 h, preferably 0 to 0.5 h, and after adding the Ti3AlC2MAX precursor, the three are continuously stirred in a water bath for 24 to 48 h, preferably 24 to 36 h, to obtain Ti3C2T x / MXene materials; FeCo nanoparticles were then combined with Ti3C2T x / MXene combined.
[0017] The sulfate and chloride of Fe and Co are FeSO4·7H2O and CoCl2·6H2O respectively, and m FeSO4·7H2O: m CoCl2·6H2O=1:4; the raw materials used are Ti3AlC2 precursor and analytically pure FeSO4·7H2O and CoCl2·6H2O; the solvent is preferably deionized water; a stirrer and a water bath are used for heating and stirring, and the stirring speed of the stirrer and the water bath is 300 to 500 r / min.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention adopts electrostatic self-assembly method to combine FeCo nanoparticles and Ti3C2T x / MXene is combined to obtain a layered composite material with simple equipment, low production cost, high production efficiency, and is green and pollution-free.
[0020] 2. Scanning electron microscopy and Raman spectroscopy show that the product prepared by the method is a composite material with a layered structure. x The interlayer spacing of the / MXene material is 170nm, and the FeCo nanoparticles are 15-20nm; the successful preparation of the composite material was further confirmed by X-ray diffraction (XRD) spectroscopy.
[0021] 3. The prepared FeCo nanoparticles and Ti3C2T x The layered composite material samples obtained by combining / MXene do not require subsequent treatment.
[0022] 4. In the range of 170 to 220 GHz, the product prepared by the method of the present invention is conducive to multiple reflections and scattering of terahertz waves due to the introduction of FeCo nanoparticles. The composite material is a high-reflection, low-absorption material in the 170 to 220 GHz frequency band, with an absorption rate of 10 to 30%.
[0023] 5. In the range of 0.2 to 3 THz, the product prepared by the method also has a wave absorbing effect, and the absorption coefficient is 100 to 150 cm -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x X-ray diffraction spectrum of the composite material combined with / MXene;
[0025] Figure 2 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x Raman spectrum of the composite material combined with / MXene;
[0026] Figure 3 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2Tx X-ray photoelectron spectroscopy of composite materials combined with / MXene;
[0027] Figure 4 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x Magnetic properties spectrum of composite materials combined with / MXene;
[0028] Figure 5 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x Scanning electron microscope image of the composite material combined with / MXene;
[0029] Figure 6 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x The relationship between the frequency and transmittance of the composite material combined with / MXene in the frequency band of 170-220GHz;
[0030] Figure 7 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x The relationship between the frequency and reflectivity of the composite material combined with / MXene in the frequency band of 170-220GHz;
[0031] Figure 8 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x The relationship between frequency and absorptivity of the composite material combined with / MXene in the frequency band of 170-220GHz;
[0032] Fig. 9 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x The relationship between the frequency and transmittance of the composite material combined with / MXene in the frequency range of 0.2 to 3 THz;
[0033] Fig.10 In Example 1, magnetic nanoparticles and two-dimensional layered structure Ti3C2T x The relationship between the frequency and the absorption coefficient of the composite material combined with / MXene in the frequency range of 0.2 to 3 THz;
[0034] Fig.11 .Ti3AlC2 and Ti3C2T x X-ray diffraction spectrum of the hybrid material of / MXene. DETAILED DESCRIPTION
[0035] The embodiment adopts m FeSO4·7H2O: m CoCl2·6H2O=1:4 prepared FeCo nanoparticles and Ti3C2T x Composite materials with layered structures combined with / MXene
[0036] In the following examples, unless otherwise specified, m1 represents the mass of the sulfate of metal Fe, and m2 represents the mass of the chloride of metal Co. FeCo nanoparticles are prepared by a hydrothermal method using analytically pure FeSO4·7H2O and CoCl2·6H2O; Ti3C2T nanoparticles are prepared by an in-situ etching method using a Ti3AlC2 precursor in a HCl+LiF mixed solution. x / MXene materials; FeCo nanoparticles and Ti3C2T3 were assembled by electrostatic self-assembly x / MXene is combined to obtain a composite material.
[0037] Example 1
[0038] First, a certain amount of polyethylene glycol was dissolved in 10-30 mL of deionized water and stirred to obtain a solution. Then, a certain amount of cyclohexane, FeSO4·7H2O (Fe 3+ ) and CoCl2·6H2O(Co 2+ ) is added to the above mixed solution to dissolve (m1:m2=1:4), and then the mixed solution is preheated at a temperature of 60-90°C for 3-6 minutes. After the preheating is completed, a certain mass of sodium hydroxide and a certain volume of hydrazine hydrate are added to obtain a uniform mixed solution. The mixed solution is transferred to a polytetrafluoroethylene-lined hydrothermal reactor and heated at a temperature of 100-130°C for 2-4 hours. After the hydrothermal reaction is completed, the lower layer product is washed with anhydrous ethanol and then with deionized water and the product is collected, and then the product is placed in an oven and dried under vacuum conditions for 10-14 hours to finally obtain spherical FeCo nanoparticles.
[0039] The Al layer elements in the Ti3AlC2 precursor were etched to obtain Ti3C2T by using the in-situ HF production method. x / MXene material, a certain mass of LiF is dissolved in a certain volume of hydrochloric acid and stirred thoroughly. After LiF is completely dissolved, Ti3AlC2 powder is added in small amounts and multiple times. Then, the mixed solution is placed in a water bath and stirred at 30-45°C for 24-48 hours. After the reaction is complete, the mixed solution is repeatedly washed with deionized water under the condition of centrifugation at 4000-6000r for 5-8min until the pH value is about 5-6. Finally, the supernatant is retained to obtain a layered structure of Ti3C2T x / MXene solution.
[0040] The composite material is made by electrostatic self-assembly of spherical FeCo nanoparticles and Ti3C2T x / MXene is combined. First, a certain volume of polydimethyl ammonium chloride solution is measured, and then a certain mass of FeCo nanoparticles are ultrasonically dispersed in the PDDA solution to make them carry positive charges. Secondly, the FeCo mixed solution is poured into the Ti3C2T x / MXene supernatant. Finally, the mixed solution was filtered using a vacuum filtration device to obtain FeCo-Ti3C2T x / MXene composites.
[0041] Comparative Example 1
[0042] The Al layer elements in the Ti3AlC2 precursor were etched to obtain Ti3C2T by using the in-situ HF production method. x / MXene material, a certain mass of LiF is dissolved in a certain volume of hydrochloric acid and stirred thoroughly. After the LiF is completely dissolved, Ti3AlC2 powder is added in small amounts and multiple times. Then, the mixed solution is placed in a water bath and stirred at 30-45°C for 24-48 hours. After the reaction is complete, the mixed solution is centrifuged at 4000-6000r for 5-8 minutes and repeatedly washed with deionized water until the pH value is about 3-4. Ti3C2T x / MXene materials, only Ti3AlC2 and Ti3C2T x / MXene hybrid materials.
[0043] Figure 1 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x The X-ray diffraction spectrum of the composite material combined with / MXene not only shows the x Typical diffraction peaks of Mg / MXene materials and the diffraction peak of FeCo were also observed.
[0044] Figure 2 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x The Raman spectrum of the composite material combined with / MXene shows that the composite material not only has Ti3C2T x / MXene material has typical Raman peaks, and also has FeCo Raman peaks.
[0045] Figure 3 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x X-ray photoelectron spectrum of the composite material combined with / MXene. It can be observed from the figure that the composite material has x In addition to the C, Ti, and O elements contained in / MXene materials, there are also Fe and Co elements.
[0046] Figure 4 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x From the magnetic energy spectrum of the composite material combined with / MXene, it can be observed that the composite material has soft magnetic characteristics.
[0047] Figure 5 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x SEM of the composite material combined with Ti3C2T / MXene. It can be observed from the figure that the composite material is also a layered structure. x There are obvious FeCo nanoparticles on the surface and between the layers of / MXene. The particles are spherical at the nanoscale and are evenly distributed, indicating that the prepared FeCo particles have successfully reacted with Ti3C2T x / MXene combined.
[0048] Figure 6 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x The relationship between frequency and transmittance of the composite material combined with / MXene in the frequency band of 170-220 GHz shows that the average transmittance of the composite material is 20%, so the incident terahertz wave shows reflection or absorption after interacting with the material.
[0049] Figure 7 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x The relationship between frequency and reflectivity of the composite material combined with / MXene in the frequency band of 170-220 GHz shows that the reflectivity of the composite material in this frequency band shows a trend of first decreasing and then increasing, with the lowest reflectivity being 50%.
[0050] Figure 8 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x The relationship between frequency and absorptivity of the composite material combined with / MXene in the frequency band of 170-220 GHz shows that the absorptivity of the composite material in this frequency band increases first and then decreases, with the highest absorptivity being 30%.
[0051] Fig. 9 The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x The relationship between the frequency and transmittance of the composite material combined with / MXene in the frequency band of 0.2-3THz shows that the transmittance is 0.5 in the two frequency bands of 0.2-05THz and 0.5-0.8THz, while the transmittance in other ranges is almost zero.
[0052] Fig.10The results show that the magnetic nanoparticles are combined with the two-dimensional layered structure Ti3C2T x The relationship between the frequency and the absorption coefficient of the composite material combined with / MXene in the 0.2-3 THz frequency band. The absorption coefficient of the composite material is 100-150 cm -1 , which shows that in Ti3C2T x Loading FeCo particles on MXene materials is beneficial to the absorption of terahertz waves by the materials.
[0053] Fig.11 Ti3AlC2 and Ti3C2T are given x X-ray diffraction spectrum of the mixed material of Ti3C2T x The diffraction peaks of Ti3AlC2 / MXene can also be observed, indicating that Ti3C2T x / MXene materials.
[0054] Matters not covered by the present invention are known technologies.
[0055] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A layered Ti3C2T x / MXene-loaded FeCo nanoparticle composite material, characterized by: The layered Ti3C2T x The structure of the MXene-loaded FeCo nanoparticle composite material is composed of magnetic nanoparticles and Ti3C2T x The layered structure of the composite material is composed of FeCo magnetic nanoparticles, which are loaded into Ti3C2T x / Interlayer and surface of MXene materials.
2. The layered Ti3C2Tx / MXene-loaded FeCo nanoparticle composite material according to claim 1, characterized in that: The FeCo loading mass percentage in the composite material structure is 10-30wt.%.
3. The layered Ti3C2Tx / MXene-loaded FeCo nanoparticle composite material according to claim 1, characterized in that: The interlayer spacing of the composite material structure is 150-190 nm; the diameter of the FeCo magnetic nanoparticles is 15-20 nm.
4. A method for preparing a layered Ti3C2Tx / MXene-loaded FeCo nanoparticle composite material as claimed in claim 1, characterized in that: Firstly, FeCo spherical nanoparticles were prepared from Fe and Co sulfates and chlorides by hydrothermal method. Secondly, Ti3AlC2 was used as a precursor and Ti3C2T was prepared by HCl+LiF in-situ etching. x / MXene materials; finally, the electrostatic self-assembly method was used to prepare magnetic nanoparticles and two-dimensional layered structure Ti3C2T x / MXene combined composite materials.
5. The method for preparing the layered Ti3C2Tx / MXene-loaded FeCo nanoparticle composite material according to claim 4, characterized in that: The mass ratio of Fe and Co sulfate to chloride is 1:4, and FeCo nanoparticles are obtained by solvothermal method; the mixed solution of HCl+LiF is stirred in a stirrer for 0-1h, and after adding Ti3AlC2 precursor, the three are stirred in a water bath for 24-48h to obtain Ti3C2T x / MXene materials; FeCo nanoparticles were then combined with Ti3C2T x / MXene combined.
6. The method for preparing the layered Ti3C2Tx / MXene-loaded FeCo nanoparticle composite material according to claim 5, characterized in that: The mixed solution of HCl+LiF is preferably stirred in a stirrer for 0 to 0.5 h. After the Ti3AlC2 precursor is added, the three are continuously stirred in a water bath for preferably 24 to 36 h.
7. The method for preparing the layered Ti3C2Tx / MXene-loaded FeCo nanoparticle composite material according to claim 5, characterized in that: The sulfate and chloride of Fe and Co are FeSO4·7H2O and CoCl2·6H2O respectively, and m FeSO4·7H2O :m CoCl2·6H2O =1:4; the raw materials used are Ti3AlC2 precursor and analytically pure FeSO4·7H2O and CoCl2·6H2O; the solvent is preferably deionized water; a stirrer and a water bath are used for heating and stirring, and the stirring speed of the stirrer and the water bath is 300 to 500 r / min.
8. Use of the layered Ti3C2Tx / MXene-loaded FeCo nanoparticle composite material according to claim 1 as a wave absorbing material in the frequency band between 170-220 GHz and 0.2-3 THz.
Citation Information
Patent Citations
Preparation method of FeCo alloy absorbing material
CN103667887A
Controllable preparation method of ferrocobalt magnetic nanoparticles with various morphologies and high saturation magnetic induction intensity
CN108723383A
MXene-magnetic metal composite material and preparation method thereof
CN109712769A
FeCo@MXene core-shell structure composite wave-absorbing material and preparation method thereof
CN110283570A
MXene / Ni composite material as well as preparation method and application thereof
CN112225220A
Cited By
Preparation method and application of high-performance wave-absorbing material FeS2 / MXene composite material
CN121342094A